Jeffersoniańska koncepcja uniwersytetu - Czarnocka, Jolanta (Acta Universitatis Lodziensis. Folia Historica, 1985)
The Jeffersonian vision of the educational system in America found its application in the Virginia University founded in 1825. Thomas Jefferson's educational concepts were formed since the time he commenced his academic studies in William and Mary College through elaboration of projects concerning dissemination of knowledge, publication of Notes on Virginia until finally they assumed a concrete shape in the University. The character of these ideas was affected by Th. Jefferson's stay in Paris and his exchange of ideas with many eminent representatives of the European Enlightement (e.g. J. A. Condorcet, J. Priestley, C. F. Volney). They were implemented in one point i.e. through creation оf a new university from its very foundations and not through reform of the already existing university. Progressive character of the Virginia University is reflected in principles, methods, and contents of curricula carried out by it. Moreover, it combined academic education with social education, introduced secularity and democratization of life at the University. The curriculum incorporated also new subjects such as exact sciences, agricultural science, modern languages, and political sciences. The mother tongue, by pushing out Latin, became the language in which lectures and seminars were conducted. Hierarchy of faculties was abolished and students wore allowed freedom in choosing subjects they wished to study. The architecture of the University was adapted to needs and requirements of academic programmes. Erection of an imposing library building – source of knowledge rising above the other buildings grow to the rank of a symbol. Th. Jefferson's reformatory activity is supported by abundant source materials (writings, papers, letters) and has received a great deal of attention in its literature.